Окремі методологічні аспекти дослідження провадження за нововиявленими або виключними обставинами - Мурзановська, Аліна Владиславівна; Мурзановська, А. В.; Murzanovska, Alina V.; Murzanovska, A. V. (Одеса : Гельветика, 2020)
У статті розглянуто питання щодо окремих методологічних аспектів дослідження провадження за нововиявленими або виключними обставинами, що пов’язано, з одного боку, з новелізацією глави 34 КПК України, а з іншого – необхідністю визначення сутності, поняття за значення нововиявлених та виключних обставин з урахуванням практики Європейського Суду з прав людини (далі – ЄСПЛ). Проведений аналіз підстав перегляду за нововиявленими або виключними обставинами дав змогу дійти висновку про принципову зміну моделі перегляду судових рішень за нововиявленими обставинами, а також необхідність внесення змін до КПК щодо визначення переліку таких обставин, з огляду на їхню сутність, ознаки та особливості. Значна увага приділення значенню практики ЄСПЛ у процесі визначення напрямів удосконалення кримінального процесуального права з метою забезпечення його ефективного правозастосування під час здійснення відповідних проваджень. Підкреслено, що наявність такої підстави, як «встановлення міжнародною судовою установою, юрисдикція якої визнана Україною, порушення Україною міжнародних зобов’язань при вирішенні справи судом», не означає, що кожне таке рішення потягне за собою зміну або скасування будь-якого рішення, адже це відбувається, якщо Суд визнав порушення Конвенції: 1) коли потерпіла сторона і далі зазнає значних негативних наслідків рішення, ухваленого на національному рівні, – наслідків, щодо яких справедлива сатисфакція не була адекватним засобом захисту і які не можна виправити інакше ніж через повторний розгляд або поновлення провадження; 2) коли рішення Суду спонукає до висновку, що а) оскаржене рішення національного суду суперечить Конвенції по суті, або b) в основі визнаного порушення лежали суттєві процедурні помилки чи недоліки, які ставлять під серйозний сумнів результат оскарженого провадження на національному рівні.

In the article the author considered the issue of certain methodological aspects of the research in proceedings on newly discovered or exceptional circumstances, which on the one hand is related to the amendment of Chapter 34 of the Criminal Procedural Code of Ukraine, on the other hand is concerned the need to define the essence, the concept of importance of newly discovered and exceptional circumstances, taking into account the practice of the European Court of Human Rights (hereinafter – ECtHR). The analysis of the grounds for review of newly discovered or exceptional circumstances allowed us to conclude that there is a fundamental change in the model of review of court decisions under newly discovered circumstances, as well as the need to amend the Criminal Procedural Code to determine the list of such circumstances, given their nature, features and peculiarities. Considerable attention was paid to the significance of the case law of the ECtHR in determining the areas of improvement of criminal procedural law in order to ensure its effective enforcement in the relevant proceedings. It is emphasized that the existence of such grounds as “establishment by an international judicial institution whose jurisdiction is recognized by Ukraine, violation of Ukraine’s international obligations in resolving the case by a court” does not mean that each such decision will entail change or revocation of any decision, as this occurs when the Court finds a violation of the Convention, in particular: 1) when the injured party continues to suffer significant adverse consequences of a decision taken at national level – consequences for which just satisfaction was not an adequate remedy and cannot be remedied other than by repeated consideration or resumption of proceedings; 2) where the judgment of the Court leads to the conclusion that a) the impugned decision of the national court is contrary to the Convention in substance, or b) the alleged violation was based on material procedural errors or omissions that seriously call into question the outcome of the impugned proceedings at the national level. It was proven that judicial review proceedings based on newly discovered or exceptional circumstances have an important role in ensuring the fairness of the proceedings, however, there is a need of further improvement of the methodology for determining regulations and their application, considering the importance of international legal standards and ECtHR practice.
Мурзановська А. В. Окремі методологічні аспекти дослідження провадження за нововиявленими або виключними обставинами / А. В. Мурзановська // Юридичний вісник. - Одеса : Гельветика - 2020. - № 6. - С. 90-99.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; court proceedings; review of court decisions; newly revealed circumstances; exceptional circumstances; судове провадження; перегляд судових рішень; нововиявлені обставини; виключні обставини